Service-oriented computing -- ICSOC 2017 Workshops : ASOCA, ISyCC, WESOACS, and Satellite Events, Málaga, Spain, November 13-16, 2017, revised selected papers /: ASOCA, ISyCC, WESOACS, and Satellite Events, Málaga, Spain, November 13-16, 2017, revised selected papers. (2018) - Unknown
No abstract available